Pengaruh Pengetahuan Kewirausahaan dan Keterampilan Wirausaha Terhadap Keberhasilan Usaha Coffee Shop di Kecamatan Medan Baru - Pinem, Kristopani; Mulia, Amrin; Suryani, Wan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this research is to find out how entrepreneurial knowledge influences business success, to find out how entrepreneurial skills influence business success and to find out how entrepreneurial knowledge and entrepreneurial skills influence the success of coffee shop businesses in Medan Baru sub-district. The population in this study was all 256 coffee shops. The sample in the research was 72 coffee shops taken using the Slovin formula. The data collection technique used in this research was carried out by distributing questionnaires. The analysis techniques used in this research are multiple linear regression, partial test (t test), simultaneous significance test (F test) and coefficient of determination. The results of the research show that entrepreneurial knowledge has a positive and significant effect on business success, entrepreneurial skills have a positive and significant effect on business success and entrepreneurial knowledge and entrepreneurial skills have a significant and simultaneous effect on the success of coffee shop businesses in Medan Baru sub-district